Book Review: Sustainable Development – Linking Economy, Society and Environment by Tracey Strange and Anne Bayley. (4th September 2009) - Springett, Delyse
Sustainable Development – Linking Economy, Society and Environment, by Tracey Strange and Anne Bayley. Paris, OECD, 2008. 142pp. ISBN: 9789264047785